2017
DOI: 10.2337/dc17-1349
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Histologic Characterization of Nonalcoholic Steatohepatitis in African American Patients

Abstract: Although African Americans have lower intrahepatic triglyceride accumulation, once NAFLD develops, NASH occurs as frequently, and as severe, as in Caucasian patients. Therefore, African Americans with NAFLD should be screened for NASH with the same degree of clinical resolve as in Caucasian patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 28 publications
4
34
0
Order By: Relevance
“…Moreover, studies assessing insulin resistance (IR) with state-of-the-art techniques (e.g., euglycemic clamp) have demonstrated that NAFL is a major risk factor for IR and type 2 diabetes (T2D), independent from visceral and intramyocellular lipid accumulation. (7) Ethnic differences in the prevalence of NAFLD have been reported in adults (8,9) and children, (1,10) with Hispanics showing the highest prevalence and blacks showing a relative protection from hepatic fat accumulation, even in the presence of morbid obesity and severe IR. (11) So far, no data in pediatrics are available about putative differences among the three major ethnic groups in the United States in the metabolic profile associated with NAFL and about the predictors of changes in hepatic fat fraction (HFF) over time.…”
Section: Metabolic Features Of Nonalcoholic Fatty Liver (Nafl) In Obementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, studies assessing insulin resistance (IR) with state-of-the-art techniques (e.g., euglycemic clamp) have demonstrated that NAFL is a major risk factor for IR and type 2 diabetes (T2D), independent from visceral and intramyocellular lipid accumulation. (7) Ethnic differences in the prevalence of NAFLD have been reported in adults (8,9) and children, (1,10) with Hispanics showing the highest prevalence and blacks showing a relative protection from hepatic fat accumulation, even in the presence of morbid obesity and severe IR. (11) So far, no data in pediatrics are available about putative differences among the three major ethnic groups in the United States in the metabolic profile associated with NAFL and about the predictors of changes in hepatic fat fraction (HFF) over time.…”
Section: Metabolic Features Of Nonalcoholic Fatty Liver (Nafl) In Obementioning
confidence: 99%
“…Ethnic differences in the prevalence of NAFLD have been reported in adults and children, with Hispanics showing the highest prevalence and blacks showing a relative protection from hepatic fat accumulation, even in the presence of morbid obesity and severe IR . So far, no data in pediatrics are available about putative differences among the three major ethnic groups in the United States in the metabolic profile associated with NAFL and about the predictors of changes in hepatic fat fraction (HFF) over time …”
mentioning
confidence: 99%
“…We agree that the prevalence of hepatic steatosis (fat) is lower in African Americans than it is in Caucasians (2), yet it is unclear whether the sample size of merely 67 African Americans provides adequate power to support the conclusion by Bril et al that NASH in a fatty liver occurs as frequently in blacks as it does in whites (1). In a very recent large systematic review of 34 studies and over 350,000 subjects, the risk of NASH in patients with steatosis was lower in blacks relative to Caucasians (relative risk 0.72 [95% CI 0.60-0.87]) (3).…”
mentioning
confidence: 47%
“…In Bril et al (1), the fibrosis scores were not statistically different between the ethnic groups. However, because of the aforementioned limitations between comparators, we don't believe the results are definitive.…”
mentioning
confidence: 75%
See 1 more Smart Citation